Jingmen Tick Virus in Ticks from Kenya - Ogola, Edwin O.; Kopp, Anne; Bastos, Armanda D. S.; Slothouwer, Inga; Marklewitz, Marco; Omoga, Dorcus; Rotich, Gilbert; Getugi, Caroline; Sang, Rosemary; Torto, Baldwyn; Junglen, Sandra; Tchouassi, David P. (Viruses, 2022)
Jingmen tick virus (JMTV) is an arbovirus with a multisegmented genome related to those of unsegmented flaviviruses. The virus first described in Rhipicephalus microplus ticks collected in Jingmen city (Hubei Province, China) in 2010 is associated with febrile illness in humans. Since then, the geographic range has expanded to include Trinidad and Tobago, Brazil, and Uganda. However, the ecology of JMTV remains poorly described in Africa. We screened adult ticks (n = 4550, 718 pools) for JMTV infection by reverse transcription polymerase chain reaction (RT-PCR). Ticks were collected from cattle (n = 859, 18.88%), goats (n = 2070, 45.49%), sheep (n = 1574, 34.59%), and free-ranging tortoises (Leopard tortoise, Stigmochelys pardalis) (n = 47, 1.03%) in two Kenyan pastoralist-dominated areas (Baringo and Kajiado counties) with a history of undiagnosed febrile human illness. Surprisingly, ticks collected from goats (0.3%, 95% confidence interval (CI) 0.1–0.5), sheep (1.8%, 95% CI 1.2–2.5), and tortoise (74.5%, 95% CI 60.9–85.4, were found infected with JMTV, but ticks collected from cattle were all negative. JMTV ribonucleic acid (RNA) was also detected in blood from tortoises (66.7%, 95% CI 16.1–97.7). Intragenetic distance of JMTV sequences originating from tortoise-associated ticks was greater than that of sheep-associated ticks. Phylogenetic analyses of seven complete-coding genome sequences generated from tortoise-associated ticks formed a monophyletic clade within JMTV strains from other countries. In summary, our findings confirm the circulation of JMTV in ticks in Kenya. Further epidemiological surveys are needed to assess the potential public health impact of JMTV in Kenya.